BEYOND ACADEMIC ACHIEVEMENT: OBE-BASED EDUCATION MANAGEMENT IN IMPROVING GRADUATES' EMPLOYABILITY SKILLS - Syafa'atul Habib; Siti Aisyah Dalimunthe; Nelly Hastuti; Melania Rahmi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The purpose of this study is to examine Outcome-Based Education (OBE) based educational management and its impact on the employability skills of university graduates. In Outcome-Based Education, graduates' learning outcomes are placed at the center of the educational process. Therefore, labor market demands serve as the primary guide in the formulation of curriculum, teaching methods, and assessment. The analysis in this study covers the role of Outcome-Based Education in higher education and employability skills. The method used is a descriptive qualitative approach, which involves collecting and analyzing data drawn from books, papers, articles, and other relevant documentation. The role of OBE in higher education and employability skills is derived through data reduction, data presentation, and conclusion. This study found that OBE-based educational management strengthens graduates' employability skills, problem-solving abilities, critical thinking, and leadership. Additionally, OBE addresses employability skill gaps through project-based learning, collaboration, and industry placements. The study also identified that the barriers to employability in OBE include constant curriculum changes, technological shifts, and faculty readiness. Therefore, it is clear that universities need to implement Outcome-Based Education with the aim of strengthening their educational management systems to produce competitive graduates and educate graduates who.